x+3y+7z=0 2x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 13:21:36
x+3y+7z=02x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)x+3y+7z=02x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)x+3y
x+3y+7z=0 2x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)
x+3y+7z=0 2x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)
x+3y+7z=0 2x+5y+11z=0,求(x^2+y^2+z^2)/(xy+2yz+3xz)
x+3y+7z=0 2x+5y+11z=0
x=2z,y=-3z
z=0,x=y=0分式无意义
(x^2+y^2+z^2)/(xy+2yz+3xz),z≠0
=[(2z)^2+(-3z)^2+z^2]/[(-2z*3z-2*3z*z+3*2z*z)
=(14z^2)/(-6z^2)
=-7/3
1.{x:y:z=3:4:5 2x+3y-5z=-142.{x-y-z=-1 3x+5y+7z=11 4x-y+2z=-13.{x+y=1 x+z=0 2x+y+2z=44.{x-y+z=-3 2x-y-z=-2 -3x+y+z=-15.{x-y+z=-3 3x+y-4z=6 2x+y-z=36.{x-2y+5z=16 2x+y-5z=7 2x-y+z=38
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..
x+y+z=0,3x-2y-2z=5,y-z=2x-7
X-Y-Z=0 X+Y-3Z=4 2X-5Y+7Z=21
x-y-z=-1 3x+5y+7z=11 4x-y+2z=-1 分别求出x=?y=?z=?
三元一次方程 X-y-z=-1 3x+5y+7z=11 4x-y+2z=-1 X=?Y=?Z=?
已知4x-3y-6z=0,x+2y-7z=0,求5x+2y-z/2x-3y-10z
已知x+4y+3z=3x-2y-5z=0,求x+2y-z/2x-3y+7z的值
已知:x+y+z=0,5x-3y-z=0,求:5x-y+z/2x+8y+7z 的值
三元一次方程解 1.{x+y-z=5 {3x+2y+z=2 {2x-2y+z=-31.{x+y-z=5 2.{9x-5y+x=-6 3.{x-y=3 4.{x+y=3 5.{4x-2y+z=7{3x+2y+z=2 {9x+y-2z=3 {x+z=7 {y+z=4 {2x-y-3z=28{2x-2y+z=-3 {-9x+3y-5z=0 {y-z=6 {z+x=5 {x+y-2z=13
x+y-z=3 y+z-x=5 z+x-y=7 求x,y,z
证明 :x/(y+z)+y/(z+x)+z/(x+y)>=3/2其中 x,y,z>0
{x+y+z=1;x+3y+7z=-1;z+5y+8z=-2
2x+3y-z=11 2x+y-5z=8 -2+7y+z=19
x/2=y/3=z/5 x+3y-z/x-3y+z
..1.x+y+z=26,2.4y+3z=7,y-z=1,3x+2z=17,x+2y-z=18 9x-7y=173.x-7y+3z=17 4.2x+4y+3z=95x-6y-z=24 3x-2y+5z=113x+7y-2z=1 5x-6y+7z=131.x+y+z=26,y-z=1x+2y-z=18 2.4y+3z=7,3x+2z=11,9x-7y=17 3.x-7y+3z=17 5x-6y-z=24 3x+7y-2z=14.2x+4y+3z=93x-2y+5z=11 5x-6y+7z=13
已知x+2y-3z=0,5x-6y+7z=1;则x:y:z=?把“5z-6y+7z=1”改成“5x-6y+7z=0”
三元一次方程组 x+y+z=6 x-z=2 2x-y+z=5 三元一次方程组x+y-z=-3 2x+y-3z=-2 3x-y+2z=-11三元一次方程组5z-4y=0 3y-5z=0 2x-y+z=6